Rocky II (1979) [videorecording (DVD)] - Stallone, Sylvester; Shire, Talia; Weathers, Carl; Meredith, Burgess, 1907-1997 (MGM DVD, 2006)
Rocky, having sustained massive injuries in his win against heavyweight champion, Apollo Creed, announces his retirement. But he soon realizes he can't escape his true calling, and prepares for the fight of his life.